Is the Diagnosis of 5th Metatarsal Fracture Type Consistent? An Inter-Observer Reliability Study. Issue 4 (November 2022) - Chapman, James; Choudhary, Zain A.; Gupta, Shubhi; Davies, Thomas; Airey, Grace L.; Mason, Lyndon W.
Category: Midfoot/Forefoot; Trauma Introduction/Purpose: Treatment pathways of 5th metatarsal fractures are commonly directed based on fracture classification, with Jones types for example, requiring closer observation and possibly more aggressive management. Our primary objective was to investigate the reliability of assessment of subtypes of 5th metatarsal fractures by different observers. Methods: Patients were identified from our prospectively collected database. We included all patient referred to our virtual fracture clinic with a suspected or confirmed 5th metatarsal fracture. Plain AP radiographs were reviewed by two observers, who were initially trained on the 5th metatarsal classification identification. Zones were defined as Zone 1.1, 1.2, 1.3, 2, 3, diaphyseal shaft (DS), distal metaphysis (DM) and head. Patients were excluded from analysis if neither observer could identify a fracture or if one or more observers could not access the images. An inter-observer reliability analysis using Cohen's Kappa coefficient was carried out, and degree of observer agreement described using Landis & Koch's description. All data was analysed using IBM SPSS v.27. Results: 1360 patients who met the inclusion criteria were identified. The two observers had moderate agreement when identifying fractures in all zones, apart from zone 1.2 and DM fractures, which only achieved 'fair' agreement (K=.308 and .381 respectively). Zones 1.1 (K=.538), 1.3 (K=.511), 2 (K=.515), 3 (K=.57), DS (K=.545) and Head (K=.558) all tended towards but did not achieve substantial agreement. Slight agreement with the next proximal and distal adjacent zones were found in Zones 1.1, 1.2 and 1.3. Slight agreement with the adjacent distal zone was found in Zone 2 and DM fractures. Zone 3 has slight agreement with Zone 2 proximally and there is an apparent difficulty with distal DS fractures resulting in a lot of crossover with DM, achieving a fair level of agreement (DS 312 vs 196; DM 120 vs 237; K=.398, p<.001). Conclusion: Reliability of sub-categorising 5th metatarsal fractures using standardised instructions conveys moderate agreement in most cases. If the region of the fracture is going to be used in an algorithm to guide a management plan and clinical follow up during a virtual clinic review, defining fractures of zones 1-3 needs careful consideration.